Pengaruh Arus Kas dan Profitabilitas terhadap Kinerja Keuangan Perusahaan Manufaktur di BEI - Berliana Rinova Putri; Nadia Safira; Dalila Nurfaida; Nadhira Camilla Putri (Badan Penerbitan Fakultas Pertanian Universitas Ratu Samban, 2026)
This study aims to analyze the influence of cash flow and profitability on the financial performance of manufacturing companies listed on the Indonesia Stock Exchange (IDX) for the period 2020–2024. The independent variables consist of operating cash flow, investing cash flow, financing cash flow, Return on Assets (ROA), Return on Equity (ROE), and Net Profit Margin (NPM), while the dependent variable is financial performance measured by Tobin’s Q ratio. This study employs a quantitative method with a panel data approach. The research population encompasses all manufacturing companies listed on the IDX, with 10 companies selected through purposive sampling over five years, yielding 50 observations. Data were processed using SPSS version 26 with multiple regression analysis, classical assumption tests, coefficient of determination, as well as partial and simultaneous significance tests. The results show that operating cash flow and ROA positively and significantly influence financial performance, while investing cash flow has a significant negative effect. ROE and NPM have positive effects but are not consistently significant across all test models. Simultaneously, all independent variables significantly affect financial performance with an F-value of 18.743 at a significance level of 0.000. The coefficient of determination (R²) of 0.718 indicates that 71.8% of the variation in financial performance can be explained by the variables in the model.